Manajemen Penanggulangan Kemacetan Transportasi Publik Di Dinas Perhubungan Kota Manado - Sambuaga, Ranno (JURNAL ILMIAH SOCIETY, 2016)
Basically, the development of large cities in developing countries face the problem of the dichotomy of development physically, economically and socially. The high rate of urbanization is characterized by high population growth rate to bring the various implications and issues on urban space resources will increase dramatically. Congestion is a universal problem caused by population growth, technological developments and other, this problem must be a demand for the government and is a crucial issue in any city in the world, in Indonesia especially specifically in the city of Manado, this study is to analyze the alleviation of congestion of public transport in the Department of Transportation the city of Manado, this study used qualitative research methods. From the research results can be seen that the reduction of congestion at the Department of Transportation in Manado is sufficient maximum